The day the Great War ended, 24 July 1923 the civilianization of war - Winter, Jay 1945- (Greater war, 1912-1923, 2022)
On 24th July 1923 the last Treaty ending hostilities in the Great War was signed at Lausanne in Switzerland. Jay Winter tells the story of the peace conference, and its outcome. He shows how peace came before justice, and how the conference and the Treaty set in motion forces leading to the global war that followed in 1939